Efficacy of Telenomus podisi Ashmead, 1893 (Hymenoptera: Platygastridae) release for the control of Euschistus heros (Fabricius, 1794) (Hemiptera: Pentatomidae) eggs in soybean, in Brazil - Pernambuco Filho, José C. A. [UNESP]; Almeida, Wellington S. M. [UNESP]; Gladenucci, Joanina; Zachrisson, Bruno; de Oliveira, Regiane Cristina [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2022)
This study aimed to assess the effectiveness of releases of different amounts of Telenomus podisi for the control of Euchistus heros in soybean crops. In addition, productivity was determined between treatments. The experiments were conducted in commercial areas of soybean production during the 2017/2018 crop season. The experiments were installed in three experimental areas in different locations of São Paulo state, Brazil; Pardinho (Farm Santa Fe), Tatuí (Farm Dos Lagos), and Angatuba (Farm Santa Irene). The experimental design was that of random blocks with five treatments and five repetitions. The statistical analysis of the experimental data applied was of variance homogeneity (Hartley Test), variance analysis (ANOVA), and Tukey’s average discrimination test, at 5% of probability. The treatments evaluated were: T1-2,000 eggs/ha; T2-3,500 eggs/ha; T3-5,000 eggs/ ha; T4-6,500 eggs/ha; T5-Control (Without T. podisi release). The release of adult parasitoids was carried out manually in the center of the plots. The parasitoid release interval was made from the presence of two nymphs or average adults of E. heros per linear meter, considering the end of the vegetative phase and physiological maturation. The sampling of nymphs and adults of E. heros were performed at weekly intervals (1, 7, 14, and 21 days) prior to the releases of T. podisi. The reduction in the number of nymphs and adults of E. heros, following the release of parasitoids was assessed. Additionally, productivity between treatments was evaluated. The release of 6,500 adults of T. podisi significantly reduced the number of nymphs and adults of E. heros and showed to be more effective regarding other treatments. The productivity between the treatments evaluated did not show significant statistical differences.
Eficacia de la liberación de Telenomus podisi Ashmead, 1893 (Hymenoptera: Platygastridae) para el control de huevos de Euchistus heros (Fabricius, 1794) en soja, en Brasil
Keywords: Applied biological control; egg parasitoids; integrated management of pests